Sustained virological response to Do hepatitis C DAA treatments in migrants and non-migrants groups. (13th November 2019) - Djaogol, T; Fontaine, H; Baudoin, M; Protopopescu, C; Marcellin, F; Dorival, C; Bourlière, M; Delarocque-Astagneau, E; Carrat, F; Carrieri, P
Abstract: Background: Although the efficacy of direct acting antivirals (DAA) against hepatitis C (HCV) has been widely proven, data lack on their effectiveness in the most vulnerable groups. In France, despite universal health coverage, migrants cumulate vulnerabilities including delays in screening that may affect both access to care and treatment effectiveness. We tested whether DAA-treated migrants had sustained virological response (SVR) rates comparable to not-migrants. Methods: We used data collected in chronic HCV-infected patients of the ANRS CO22 HEPATHER cohort, receiving a first treatment with DAA, with follow-up from 2012 until 2022. SVR was measured by PCR, 12 weeks after the end of treatment. The main covariate was a 4-category variable comparing migrants and non-migrants, with or without other vulnerability conditions (including drug use, unhealthy alcohol use, living in poverty, being a man who have sex with men). We used a Poisson regression model to assess the relationship between this covariate and SVR after adjustment for significant predictors and potential confounders. Results: The analysis included 5, 080 individuals, of which 17% classified as migrants with at least one vulnerability, 10% as migrants with no vulnerability, 39% as non-migrants with at least one vulnerability and 35% as non-migrants with no vulnerability. Median [IQR] age was 57 [51-65] years, 56% of individuals were men, and 96% had SVR. The multivariable analysis showed no significant difference between the 4-category covariate and SVR. In addition, we found that SVR rates increased steadily during follow-up. Conclusions: This is the first analysis exploring differences in SVR rates among migrants and not-migrants. The lack of significant differences found despite the power of the study suggests that migrants respond to DAA treatment as well as any other group of HCV-infected patients. These data can help advocating better screening and access to treatment for HCV-infected migrants in France. Key messages: No significant differences were observed between migrants and non-migrants in terms of effectiveness of DAA treatment. These findings can help improving access to HCV care for migrants.